2020
DOI: 10.1111/cdoe.12517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of third molars determined by panoramic radiographs in a population‐based survey of adult Finns

Abstract: Objectives:The aim of the study was to examine the prevalence of third molars in panoramic radiographs in a population-based study of adults aged ≥30 years. Methods:Out of a sample of 8028 inhabitants of Finland, selected with two-staged stratified cluster-sampling method for the Health 2000 Survey, 5989 participated in clinical oral examination and panoramic radiography. Mean age was 52.5 years (SD 14.6; range 30-97 years). The following variables were included in the analysis: participant characteristics, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
2
2
Order By: Relevance
“…Ventä et al . reported a lower rate than the present study by including individuals over 30 years of age ( 16 ). The diagnostic method used also had an effect on prevalence.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Ventä et al . reported a lower rate than the present study by including individuals over 30 years of age ( 16 ). The diagnostic method used also had an effect on prevalence.…”
Section: Discussioncontrasting
confidence: 89%
“…Although some studies reported that there was no difference between gender and the prevalence of impacted third molars ( 16 , 24 ), most studies, including the present study, stated that the frequency of impacted third molars was significantly higher in females ( 25 ). The higher prevalence rates of impacted third molars in females can be attributed to the smaller size of the jaw compared to males and the lack of space for eruption.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations